RNF12 Activates Xist and Is Essential for X Chromosome Inactivation - Barakat, Tahsin Stefan (Public Library of Science, 2011)
In somatic cells of female placental mammals, one of the two X chromosomes is transcriptionally silenced to accomplish an equal dose of X-encoded gene products in males and females. Initiation of random X chromosome inactivation (XCI) is thought to be regulated by X-encoded activators and autosomally encoded suppressors controlling Xist. Spreading of Xist RNA leads to silencing of the X chromosome in cis. Here, we demonstrate that the dose dependent X-encoded XCI activator RNF12/RLIM acts in trans and activates Xist. We did not find evidence for RNF12-mediated regulation of XCI through Tsix or the Xist intron 1 region, which are both known to be involved in inhibition of Xist. In addition, we found that Xist intron 1, which contains a pluripotency factor binding site, is not required for suppression of Xist in undifferentiated ES cells. Analysis of female Rnf12(−/−) knockout ES cells showed that RNF12 is essential for initiation of XCI and is mainly involved in the regulation of Xist. We conclude that RNF12 is an indispensable factor in up-regulation of Xist transcription, thereby leading to initiation of random XCI.